1995
DOI: 10.1111/j.1365-2249.1995.tb03729.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody response to the Ro/La particle may predict outcome in neonatal lupus erythematosus

Abstract: SUMMARYThis study was undertaken to determine the role of antibodies against both recombinant Ro (r-Ro) and La (r-La) proteins and polypeptides derived from the recombinant La protein in predicting fetal and neonatal outcome in children at risk to develop neonatal lupus erythematosus (NLE). All sera were obtained in the perinatal period and quantitative ELISA assays were used. We collected 41 maternal sera within 2 months of delivery ofa child with NLE (21 with congenital heart disease block (CHB) and 20 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…Previous studies have shown that all cases of cardiac NLE are associated with antibodies to at least 1 of the 52-and 60-kD Ro-particles and/or to the 48-kD La-protein (8,9). More recently, the response to peptides within the Ro-and La-proteins has also been examined (9,25,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that all cases of cardiac NLE are associated with antibodies to at least 1 of the 52-and 60-kD Ro-particles and/or to the 48-kD La-protein (8,9). More recently, the response to peptides within the Ro-and La-proteins has also been examined (9,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…It took another 20 years before this association became well recognized (3)(4)(5) and until the early 1980s that studies documented a close association between maternal anti-Ro/SSA and anti-La/SSB antibodies and congenital heart block (6,7). It was subsequently shown that the highest relative risks of CAVB were seen in offspring of mothers with antibodies against 52-kD Ro and 48-kD La proteins (8,9).…”
mentioning
confidence: 99%
“…In addition to the traditional Ro antigen of 60kD, another antigen of 52kD has been identified. Antibodies with specificity for the 52 kD component of the SSA/Ro protein (Ro52) are more frequently found and are present at higher concentrations in the serum of children with congenital heart block and their mothers [14,15]. More specifically, maternal anti Ro-52 kD antibodies with primary specificity for a particular peptide fragment (amino acids 200 through 239, p200-239) are significantly associated with the development of CHB [15,16].…”
Section: Pathogenesismentioning
confidence: 99%
“…In addition to inducing tissue damage, anti-SSA/Ro and/or anti-SSB/La antibodies inhibit calcium channel activation or the cardiac L-and T-type calcium channels themselves. L-type channels are crucial to action potential propagation and conduction in the AV node [Xiao GQ, 2001;Silverman, 1995]. Very few neonates who have maternal antibodies develop neonatal lupus.…”
Section: Pathogenesis Of Chb In Nlementioning
confidence: 99%
“…Post mortem studies in the neonates revealed deposition of IgG1 & IgG3 along with complement (including C1q, C4, C3d, C6, and C9), and fibrin [6. Silverman, 1995;Salomonsson 2002] leading initially to pancarditis and later on to fibroelastosis of the heart. Thus it can involve almost all the structures of the heart.…”
Section: Pathogenesis Of Chb In Nlementioning
confidence: 99%